Blastemal predominant type Wilms tumor in Japan: Japan Children's Cancer Group. Issue 4 (16th April 2019) - Koshinaga, Tsugumichi; Takimoto, Tetsuya; Okita, Hajime; Tanaka, Yukichi; Inoue, Eisuke; Oue, Takaharu; Nozaki, Miwako; Tsuchiya, Kunihiko; Haruta, Masayuki; Kaneko, Yasuhiko; Fukuzawa, Masahiro
Abstract: Background: Persistence of blastemal components after chemotherapy is a marker of poor outcome in Wilms tumor (WT). Recent reports from local Japanese areas have described pre‐chemotherapy blastemal predominant type WT to also be a risk factor for relapse. The significance, however, of blastemal predominant WT remains to be evaluated in a larger study. This study retrospectively evaluated the prognostic significance of pre‐chemotherapy blastemal predominant type WT in the Japan Wilms tumor Study (JWiTS) trials. Methods: The JWiTS trial (1996–2013) was a prospective, single‐arm study. The outcomes of blastemal predominant type WT were retrospectively evaluated compared with non‐blastemal type WT excluding anaplasia between 1996 and 2013. Relapse‐free survival (RFS) and overall survival (OS) were estimated. Results: Of 319 primary renal tumors diagnosed by the central pathology review system, advanced stage of pre‐chemotherapy blastemal predominant type WT ( n = 53; 16.1%) occurred more frequently in older children than non‐blastemal type WT ( n = 225), and was especially frequent in female patients registered in the JWiTS trials. No significant difference in 10 years RFS and OS (78.8% vs 84.5; P = 0.201) or in 10 years RFS and OS (89.3% vs 93.5; P = 0.45) was seen between pre‐chemotherapy blastemal predominant type and non‐blastemal type WT. Conclusions: Relapse‐free survival and OS are not significantly different between pre‐chemotherapy blastemal predominant type and non‐blastemal type WT.